Literature and popular culture in early modern England (Ashgate, 2009)
"1978 witnessed the publication of Peter Burke's groundbreaking study Popular Culture in Early Modern Europe. Now in its third edition this remarkable book has for thirty years set the benchmark for cultural historians with its wide ranging and imaginative exploration of early modern European popular culture. In order to celebrate this achievement, and to explore the ways in which perceptions of popular culture have changed in the intervening years a group of leading scholars are brought together in this new volume to examine Burke's thesis in relation to England. Adopting an appropriately interdisciplinary approach, the collection offers an unprecedented survey of the field of popular culture in early modern England as it currently stands, bringing together scholars at the forefront of developments in an expanding area. Taking as its starting point Burke's argument that popular culture was everyone's culture, distinguishing it from high culture, which only a restricted social group could access, it explores an intriguing variety of sources to discover whether this was in fact the case in early modern England. It further explores the meaning and significance of the term 'popular culture' when applied to the early modern period: how did people distinguish between high and low culture - could they in fact do so?"--Publisher's description.